Intracellular invasion potential and pathogenic effects of Corynebacterium striatum clinical isolates in human airway epithelial cells - Du, Lanna; Guo, Binxin; Wen, Juan; Liu, Hui; Wang, Junrui (Frontiers in Microbiology, 2025)
BackgroundCorynebacterium striatum emerged as an important hospital acquired pathogen in recent years, but less is known about its virulence potential. This study focusses on its pathogenesis on human airway epithelial cells, since lower airway tract infection was the most frequent type of infection caused by C. striatum.MethodsWhole genome sequencing was employed to construct single nucleotide polymorphism (SNP)-based phylogenetic tree of 27 C. striatum clinical isolates and predict the carriage of virulence related genes. Adherence and invasion capabilities of these isolates toward human A549 epithelial cells were detected using antibiotic protection assay, and the pathogenic effects of C. striatum to A549 cells was detected by flow cytometry.ResultsTwenty-seven C. striatum clinical isolates were classified into five clades and 62.96% (17/27) isolates belonged to the predominant clade five, all of which carried seven virulence related genes (hmuU, irp6B, regX3, groEL, sigA, sodA, and sigH). Based on the protocol established for invasion assay in this study, 44.44, 48.15 and 7.41% isolates were classified as strongly invasive (SI), moderately invasive (MI), and weakly invasive (WI) isolates, respectively. All of the isolates could effectively invade into A549 cells during 2h infection, with varying invasion rates from 0.001% to 4.615%. The highest apoptosis rate (30.54%) was observed in A549 cells infected by the representative SI isolates (CS-51), followed by 25.56% for CS-252 (SI), 24.95% for CS-32 (MI), and 17.53% for CS-258 (MI).ConclusionsTo our knowledge, this is the first report to characterize the in vitro intracellular invasion and pathogenesis of C. striatum. All of the C. striatum isolates tested in this study could effectively invade into A549 cells and the representative isolates displayed obvious cytotoxicity with varying degrees. The contribution and mechanism of specific virulence-related genes in mediating intracellular invasion in C. striatum needs further investigation, especially for spaDEF.